2012
DOI: 10.5296/jbls.v3i1.1961
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stone Dust Exposure on Some Liver and Kidney Related Serum Parameters of Stone Crush Plant Workers

Abstract: In the present study the effects of stone dust exposure on liver and kidney related serum parameters were assessed in workers of stone crush plants in various localities of Swat and Dir (L) districts of Khyber Pakhtunkhwa, Pakistan. The liver and kidney related serum parameters included Glutamate Pyruvate Transaminase (GPT), Alkaline Phosphatase (ALP), bilirubin and creatinine. Blood samples were collected from 66 exposed workers and 66 unexposed persons (control). The mean values of liver related parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…The mean SGPT, total bilirubin and SGOT levels were significantly higher in dust exposed subjects and this is in agreement with previous work by Ilahi et al (2012). SGPT and bilirubin are localized in the liver and high amount in the serum is indicative of damages to hepatic tissues.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The mean SGPT, total bilirubin and SGOT levels were significantly higher in dust exposed subjects and this is in agreement with previous work by Ilahi et al (2012). SGPT and bilirubin are localized in the liver and high amount in the serum is indicative of damages to hepatic tissues.…”
Section: Resultssupporting
confidence: 92%
“…Degenerative tendencies observed in the lung as a result of dust exposure is a clear manifestation of damages to the lung tissues thus conforming to studies of Zhang et al, 2018 who reported pneumoconiosis and pulmonary fibrosis in tracheal and non-tracheal exposed rats respectively. Histopathological differences observed in dust exposed rats in this study is similar to reports of Ilahi et al (2012), who suggested that high levels of SGPT and bilirubin levels are clear manifestations of damaged liver cells. With the ever-increasing global population, there is resultant increase demand for food, of which poultry meat is not an exception.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Stone quarrying is an industrial process, in which rock stones are cut, crushed, and milled to produce manufactured sand, gravels, and slabs that are used for construction. These processes generate dust and respirable fine PMs made up of free silica, light, and heavy minerals[ 4 ] that lead to respiratory complications upon prolonged exposure. Hence, this study was conducted to assess the pulmonary function and to determine the associated risk factors among quarry workers of Chennai city.…”
Section: Discussionmentioning
confidence: 99%
“…Mainly, the particulates from stone quarries, when inhaled continuously, deposit in the lungs, eventually leading to respiratory conditions such as silicosis, tuberculosis (TB), and lung cancer. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%